Five actions for five people: emergency cesarean section protocol - Paolo Mannella; Federica Pancetti; Andrea Giannini; Eleonora Russo; Magdalena Montt-Guevara; Tommaso Simoncini (BMC, 2023)
Abstract Objective The scope of this work is to evaluate an operative protocol for emergency C-section to improve teamwork and reduce surgical setup time. Methods Sixty-six health care operators working together in the delivery ward (gynecologists, midwives, anesthesiologists) simulated an emergency scenario applying a "five actions for each operator" protocol. For each simulation, the decision to delivery interval was considered and the perception of each operator as a team worker was analyzed with specific tests. Results The "five actions for five people" protocol significantly reduces the decision to delivery interval (p < 0.001) for emergency C-section. At the same time, a simple and codified scheme improves communication among team members, avoids overlapping roles. Indeed, all the operators become more aware of being helpful to the team (p < 0.001). Conclusion The use of a standardized, simple, and immediately usable protocol improves the performance of the delivery room team in terms of the urgency and quality of the operator's participation in the event. Procedures of this type should be favored within emergency obstetric settings. Trial registration number CEAVNO 19-01-23. Local ethical Committee (COMITATO ETICO REGIONALE PER LA SPERIMENTAZIONE CLINICA - Sezione autonoma Area Vasta Nord Ovest -CEAVNO) approved this study as simulation training study. All the operators participated voluntary during their working time.